Nerve damage in leprosy: An electrophysiological evaluation of ulnar and median nerves in patients with clinical neural deficits: A pilot study - Sumit Kar; Ajay Krishnan; Neha Singh; Ramji Singh; Sachin Pawar (Wolters Kluwer Medknow Publications, 2013)
Background : Leprosy involves peripheral nerves sooner or later in the course of the disease leading to gross deformities and disabilities. Sadly, by the time it becomes clinically apparent, the nerve damage is already quite advanced. However, if the preclinical damage is detected early in the course of disease, it can be prevented to a large extent. Materials and Methods: We conducted an electrophysiological pilot study on 10 patients with clinically manifest leprosy, in the Dermatology Department of Mahatma Gandhi Institute of Medical Sciences, Sewagram. This study was done to assess the nerve conduction velocity, amplitude and latency of ulnar and median nerves. Results and Conclusion: We found reduced conduction velocities besides changes in latency and amplitude in the affected nerves. Changes in sensory nerve conduction were more pronounced. Also, sensory latencies and amplitude changes were more severe than motor latencies and amplitude in those presenting with muscle palsies. However, further studies are going on to identify parameters to detect early nerve damage in leprosy.